Mechanism underlying formation of SSC in optical glass due to dynamic impact of single diamond scratch - Chen, Jiang; Zhao, Hang; Zhang, Fei-hu; Zhang, Yuan-jing; Zhang, Yong (Journal of Central South University, 2015)
During the grinding of optical glass, the abrasion directly affects the morphology and depth of subsurface cracks (SSC). The effect of dynamic impact of grinding abrasives on optical glass is an important issue in the field of optics manufacturing. In this work, a single diamond scratch was used to grind optical glass, and grinding parameters were collaboratively controlled to ensure that the cutting layer remained constant. A dynamometer was used to record the duration of the impact process, and the cross-section of the test piece was polished for scanning electron microscopy (SEM) to determine the depth of the SSCs. The experimental results show that as wheel speed increases, SSC depth tends to decrease. When the wheel speed gradually increases from 500 r/min to 2500 r/min, the probability distribution curve for the maximum SSC depth shifts downward by around 80 μm. The effect of the dynamic impact of single diamond scratch is found to be an important cause of SSC formation in optical glass during grinding, i.e., the faster the grinding, the shallower the SSCs.